The Study of Compatibility between Gestalt and Social Cognitive Theory of Tertiary Level Students via Sketches at Wat Phumin, Nan Province - Pichaichanarong, Tawipas (Graduate School of Institut Seni Indonesia Yogyakarta, 2024)
The study takes place in the setting of Wat Phumin, located in Nan Province, Thailand. This revered temple has proudly maintained its magnificent presence for centuries, earning worldwide acclaim as a symbol of timeless greatness. Located in northern Thailand, Wat Phumin in the province of Nan captures the attention of visitors with its intricate connection between local people and cultural surroundings.The researcher creatively uses sketches of Wat Phumin from the website to understand how tertiary level students perceive and interact with the temple's architecture and cultural heritage. The study used quantitative methods to collect and analyze data, using percentage, mean, and Pearson correlation coefficient. This study aims to understand Gestalt and Social Cognitive Theory, cultural context's impact on cognitive processes and social learning. Urban sketching contributes to Global Goals and sustainable cities by capturing Wat Phumin, Nan Province.The main objective of this research is to enhance people's understanding of the complexities of human cognition and visual perception, with Wat Phumin in Nan Province serving as an intriguing case study. As a result, this study also set the stage for innovative pedagogical models to come.Kajian Kompatibilitas antara Gestalt dan Teori Kognitif Sosial Terhadap Siswa Tingkat Tersier Melalui Sketsa di Wat Phumin, Provinsi NanAbstrakPenelitian berlangsung di Wat Phumin, yang terletak di Provinsi Nan, Thailand. Kuil yang dihormati ini dengan bangga mempertahankan keberadaannya yang megah selama berabad-abad, mendapatkan pengakuan dunia sebagai simbol keagungan abadi. Terletak di Thailand utara, Wat Phumin di provinsi Nan menarik perhatian pengunjung dengan hubungan rumit antara masyarakat lokal dan budaya sekitarnya. Peneliti secara kreatif menggunakan sketsa Wat Phumin dari situs web untuk memahami bagaimana siswa tingkat tersier memandang dan berinteraksi dengan arsitektur candi dan warisan budaya. Penelitian ini menggunakan metode kuantitatif untuk mengumpulkan dan menganalisis data, menggunakan persentase, mean, dan koefisien korelasi Pearson. Penelitian ini bertujuan untuk memahami Gestalt dan Teori Kognitif Sosial, dampak konteks budaya terhadap proses kognitif dan pembelajaran sosial. Sketsa perkotaan berkontribusi terhadap Tujuan Global dan kota berkelanjutan dengan memotret Wat Phumin, Provinsi Nan. Tujuan utama penelitian ini adalah untuk meningkatkan pemahaman masyarakat tentang kompleksitas kognisi dan persepsi visual manusia, dengan Wat Phumin di Provinsi Nan menjadi studi kasus yang menarik. Hasilnya, penelitian ini juga membuka jalan bagi model pedagogi inovatif di masa depan.